Quality Management at Madrasah Aliyah Daarul Ikrom Pesawaran - Nurdin Hidayat; Patimah, Siti (Graduate Program Magister Manajemen Pendidikan, 2023)
Islamic educational institutions have a very large role in national education. This is because national education cannot be separated from religious values. From this, the management of madrasah institutions in order to improve the quality of Islamic Education is needed because with quality management in madrasahs the ability of madrasahs to utilize educational resources both human and non-human resources will improve the ability of educational inputs, processes and outputs to meet the requirements demanded by users of educational services. This research produced several findings, namely first, quality planning involving the foundation and all managers. Second, the implementation of quality is planned in advance by each madrasah in the form of curriculum content. Third, the implementation of quality monitoring and evaluation is carried out internally and externally. Fourth, quality improvement carried out by madrasah managers and organizers, in this case the foundation.